Rotational Thromboelastometry Rapidly Predicts Thrombocytopenia and Hypofibrinogenemia During Neonatal Cardiopulmonary Bypass. Issue 4 (July 2018) - Scott, John P.; Niebler, Robert A.; Stuth, Eckehard A. E.; Newman, Debra K.; Tweddell, James S.; Bercovitz, Rachel S.; Benson, D. Woodrow; Cole, Regina; Simpson, Pippa M.; Yan, Ke; Woods, Ronald K.
Background: Thrombocytopenia and hypofibrinogenemia during neonatal cardiopulmonary bypass (CPB) contribute to bleeding and morbidity. Rotational thromboelastometry (ROTEM) is a viscoelastic assay with a rapid turnaround time. Data validating ROTEM during neonatal cardiac surgery remain limited. This study examined perioperative hemostatic trends in neonates treated with standardized platelet and cryoprecipitate transfusion during CPB. We hypothesized that ROTEM would predict thrombocytopenia, hypofibrinogenemia, and the correction thereof. Methods: Forty-four neonates undergoing CPB were included in this prospective observational study. Blood samples were obtained at Baseline, On CPB, Post-CPB, and Postoperative . The ROTEM analysis included extrinsically activated (Extem) and fibrinogen-specific (Fibtem) assays. Platelet-specific thromboelastometry (Pltem) values were calculated. Platelet and cryoprecipitate transfusion was initiated prior to termination of CPB. Results: Platelet count and Extem amplitude decreased significantly On CPB ( P < .0001), increased significantly Post-CPB ( P < .0001), and Postoperative values were not significantly different from Baseline. Extem amplitude at 10 minutes (A10) > 46.5 mm (AUC = 0.941) and Pltem A10 > 37.5 mm [area under curve (AUC) = 0.960] predicted platelet count > 100 × 10 3 /μL, and they highly correlated with platelet count ( R = 0.89 and R = 0.90, respectively). Fibrinogen concentration and Fibtem amplitude decreased significantly On CPB ( P ≤ .0001) and normalized after cryoprecipitate transfusion. Fibtem A10 > 9.5 mm predicted fibrinogen >200 mg/dL (AUC = 0.817), but it correlated less well with fibrinogen concentration ( R = 0.65). Conclusions: ROTEM analysis during neonatal cardiac surgery is sensitive and specific for thrombocytopenia and hypofibrinogenemia, identifying deficits within 10 minutes. Platelet and cryoprecipitate transfusion during neonatal CPB normalizes platelet count, fibrinogen level, and ROTEM amplitudes.